VARIATION IN BIOFUEL POTENTIAL OF TWELVE CALOPYLLUM INOPHYLLUM POPULATIONS IN INDONESIA - Leksono, Budi; Hendrati, Rina Laksmi; Windyarini, Eritrina; Hasnah, Trimaria (Indonesian Journal of Forestry Research, 2014)
Global energy crisis raises biofuel prices significantly. It has driven the world to enhanceÃÂ  environmentally-friendly renewable-energy (biofuel) production. Calophyllum inophyllum (Nyamplung) is one of the potential biofuel sources, extracted from its seeds which can be harvested up to 50 years. Technical-practices of biofuel production for nyamplung seeds have been developed at industrial scale by cooperations in Cilacap (Java) and Energy Self-Sufficient Villages (Desa Mandiri Energi) in Banyuwangi, Purworejo, Kebumen, Ujung Kulon (Java) and Selayar (outside Java). However, there is only a limited-information available on biofuel productivity and quality from nyamplungÃÂ  populations. This paper studies the biofuel-potential-variations among 12 populations in Indonesia (6 from Java, 6 outside Java) in terms of genetically-improved seed-sources. The oil was extracted using a combination of vertical hot pressÃÂ  (VHP) and screw press expeller (SPE) followed by degumming to make refined oil, and esterification-transesterification to turn it into biodiesel. The result shows great variation of biofuel content among the population. Oil production percentage varies from 37-48,5% (VHP) and 50-58% (SPE) crude oil, 36-48% (VHP) and 40-53% (SPE) refined oil, and 17-33% (SPE) for biodiesel. The highest variation after degumming is due to high seed resin content. DNA analysis shows genetic-variations among populations from intermediate (Java) to high (ouside Java) and intermediate within populations. Information of biofuel content, DNA analysis and environmental conditions for each population are considered to be important factors to establish genetically-improved seed-sources.